Theoretical study of the thermodynamics of the mechanisms underlying antiradical activity of cinnamic acid derivatives. (25th April 2018) - Amić, Ana; Marković, Zoran; Klein, Erik; Dimitrić Marković, Jasmina M.; Milenković, Dejan
Graphical abstract: Highlights: Dihydrocinnamic acids are more potent radical quenchers than their unsaturated forms. Catechol, guaiacyl and carboxyl moieties may be involved in free radical scavenging. Double free radical scavenging mechanisms may be operative in radical inactivation. As abundant colon catabolites studied acids could be effective in vivo antioxidants. Abstract: The role of antiradical moieties (catechol, guaiacyl and carboxyl group) and molecular conformation in antioxidative potency of dihydrocaffeic acid (DHCA) and dihydroferulic acid (DHFA) was investigated by density functional theory (DFT) method. The thermodynamic preference of different reaction paths of double (2H + /2e − ) free radical scavenging mechanisms was estimated. Antiradical potency of DHCA and DHFA was compared with that exerted by their unsaturated analogs − caffeic acid (CA) and ferulic acid (FA). Cis / trans and anti- isomers of studied cinnamic acid derivatives may scavenge free radicals via double processes by involvement of catechol or guaiacyl moiety. Carboxyl group of syn -isomers may also participate in the inactivation of free radicals. Gibbs free energies of reactions with various free radicals indicate that syn -DHCA and syn -DHFA, colon catabolites that could be present in systemic circulation in low μM concentrations, have a potential to contribute to health benefits by direct free radical scavenging.